SIKAP TERHADAP KAMPANYE 100% CINTA INDONESIA, ETNOSENTRISME KONSUMEN, DAN KESEDIAAN MEMBELI PRODUK LOKAL INDONESIA - Khairani, Zulia; Abdillah, Muhammad Rasyid (Jurnal Daya Saing, 2018)
This study aims to analyze attitudes on the campaign of 100% love Indonesia, ethnosentrime level of consumers and willingness to buy local products Indonesia. Furthermore, we want to examine the influence of attitude on 100% of Indonesia love campaign and consumer ethnocentrism on willingness to buy local product of Indonesia. Smpel in this research is 100 people, taken by purposive sampling method and then analyzed to data obtained by using quantitative analysis. Quantitative analysis includes: test of validity and reliability, test of classical assumption, multiple regression analysis, hypothesis test through t test, and coefficient of determination analysis (R2). Qualitative analysis is the interpretation of the data obtained in the research and the results of data processing that has been implemented by giving explanations and explanations. The result of the research found that partially consumer ethnocentrism only had positive effect on willingness to buy local product, while together, consumer attitude and consumer ethnocentrism have positive and significant effect to the willingness to buy Indonesian local product. Keywords: Consumer Attitudes, "Buy Local" Campaign, Consumer Etnocentrism, Local Product Buying Williness